Effects of Ultrasound Implementation on Physical Examination Learning and Teaching During the First Year of Medical Education. (1st January 2015) - Dinh, Vi Am; Frederick, Jon; Bartos, Rebekah; Shankel, Tamara M.; Werner, Leonard
Abstract : Objectives: Increasing emphasis has been placed on point‐of‐care ultrasound in medical school. The overall effects of ultrasound curriculum implementation on the traditional physical examination skills of medical students are still unknown. We studied the effects on the Objective Standardized Clinical Examination (OSCE) scores of year 1 medical students before and after ultrasound curriculum implementation. Methods: An ultrasound curriculum was incorporated into the physical diagnosis course for year 1 medical students in the 2012–2013 academic year. We performed a prospective observational study comparing traditional OSCE scores of year 1 medical students exposed to the ultrasound curriculum (post‐ultrasound) versus historic year 1 medical student controls (pre‐ultrasound) with no ultrasound exposure. Questionnaire data were also obtained from year 1 medical students and physical diagnosis faculty to assess attitudes toward ultrasound implementation. Results: The final overall OSCE scores were graded with a 5‐point Likert‐type scale from unsatisfactory to outstanding. There was a significant increase in outstanding scores in the post‐ultrasound compared to the pre‐ultrasound group (27.0% versus 10.9%; P < .001). The post‐ultrasound group had significantly ( P < .05) increased first‐time pass rates on blood pressure measurements, the abdominal examination, and professionalism. Student and physical diagnosis faculty questionnaire data showed an overall positive response, with most agreeing or strongly agreeing that ultrasound should be included in the future year 1 medical student curriculum. Conclusions: Ultrasound implementation into a physical diagnosis curriculum for year 1 medical students is feasible and may improve their overall traditional physical examination skills.